An overview of advances in global maternal health: From broad to specific improvements. Issue 1 (23rd May 2019) - Khorrami, Najma; Stone, Juliana; Small, Maria J.; Stringer, Elizabeth M.; Ahmadzia, Homa K.
Abstract: After the declaration of the Millennium Development Goals in 2000 by the United Nations, many stakeholders allocated financial resources to "global maternal health." Research to expand care and improve delivery of maternal health services has exponentially increased. The present article highlights an overview, namely 10 of the health system, clinical, and technology‐based advancements that have occurred in the past three decades in the field of global maternal health. The list of topics has been selected through the cumulative clinical and public health expertise of the authors and is certainly not exhaustive. Rather, the list is intended to provide a mapping of key topics arranged from broad to specific that span from the global policy level to the level of individual care. The list of health system, clinical, and technology‐based advancements include: (10) Millennium Development Goals and Sustainable Development Goals; (9) Development of clinical training programs, including the potential for subspecialty development; (8) Prenatal care expansion and potential; (7) Decentralized health systems, including the use of skilled birth attendants; (6) Antiretroviral therapy for HIV; (5) Essential medicines; (4) Vaccines; (3) mHealth/eHealth; (2) Ultrasonography; and (1) Obstetric hemorrhage management. With the Sustainable Development Goals now underway, the field must build upon past successes to sustain maternal and neonatal well‐being in the future global health agenda. Abstract : This commentary takes a global perspective to highlight ten landmark public health and clinical advancements in the area of maternal health.